Hadith #209 - Sahih al-Bukhari - Suwayd bin al-Nu'man (Sahih al-Bukhari)
In the year of the conquest of Khaibar I went with Allah’s Messenger (ﷺ) till we reached Sahba, a place near Khaibar, where Allah’s Messenger (ﷺ) offered the `Asr prayer and asked for food. Nothing but saweeq was brought. He ordered it to be moistened with water. He and all of us ate it and the Prophet (ﷺ) got up for the evening prayer (Maghrib prayer), rinsed his mouth with water and we did the same, and he then prayed without repeating the ablution.
Grade: Sahih

Hadith #215 - Sahih al-Bukhari - Suwayd bin al-Nu'man (Sahih al-Bukhari)
In the year of the conquest of Khaibar I went with Allah’s Messenger (ﷺ) till we reached As-Sahba’ where Allah’s Messenger (ﷺ) led the `Asr prayer and asked for the food. Nothing but saweeq was brought and we ate it and drank (water). The Prophet (ﷺ) got up for the (Maghrib) Prayer, rinsed his mouth with water and then led the prayer without repeating the ablution.
Grade: Sahih